Supporting Change through Expansive Learning in Engineering Practice : paper presented at the EASST 2010 conference, 2-4 September, Trento, Italy (Track 20: Engineering Practice: Performing a Profession, Constructing Society) - Hackel, Monika [Verfasser]; Klebl, Michael [Verfasser] (My University, 2010)
"Engineering is considered as a motor of innovaton in society. However, engineering itself is always on the move and affected by change in everyday work processes. This paper presents the ethnographic examination of activity systems in mechatroni-cal engineering based on the approach of 'developmental work research' as set forth by Engeström. Engeströms specific form of 'action research' concentrates on activity systems. Contradictions and double binds force an activity system, the related community of practice and the practitioners themselves to change. They find and develop new ways to organize the division of labour and create new instruments to support this. Engeström calls this expansive learning. Difficulties in inter-disciplinary collaboration in mechatronic engineering became the starting points for change in the here presented project AQUIMO. Expansive learning has been facilitated in two respects. On the one hand, the engineers who participated in the study learned about their contradictions in everyday work, and thus discussed and implemented new ways to organize their local community of practice. On the other hand, the confrontation with the findings from the studies supported the project partners to create an innovative mechatronical modelling tool and to identify competency needs, which are addressed by qualification." (Autorenreferat, BIBB-Doku)
Keywords: S 6.2.3 Metallerzeugung und -bearbeitung, Maschinenbau, Montierberufe (inkl. fahrzeugtechnischer Berufe); T 2.3 Handlungstheorien; T 2.2 Lerntheorien; Maschinenbau; Aktionsforschung; Lernforschung; Arbeitswissenschaft; Interdisziplinarität